G Protein-Coupled Receptor Kinase 2 (GRK2) Regulates T Cell Response in a Murine Model of House Dust Mite-Induced Asthma - Kammala, Ananth K.; Yang, Canchai; Panettieri, Reynold A.; Das, Rupali; Subramanian, Hariharan (Frontiers in Allergy, 2021)
G protein-coupled receptor kinase 2 (GRK2) is an adapter protein that modulates G protein-coupled receptor (GPCR) signaling. It also regulates the functions and activity of other intracellular proteins in many cell types. Accordingly, GRK2 is thought to contribute to disease progression by a variety of mechanisms related to its multifunctional roles. Indeed, GRK2 levels are enhanced in patient samples as well as in preclinical models of several diseases. We have previously shown that GRK2 regulates mast cell functions, and thereby contributes to exacerbated inflammation during allergic reactions. In the current study, we observed that GRK2 levels are enhanced in the lungs of human asthma patients and in mice sensitized to house dust mite extract (HDME) allergen. Consistent with these findings, interleukin (IL)-4 and IL-13 levels were reduced in the lungs of GRK2+/− mice in a HMDE mouse model of asthma. Because Th2 cells are the major source of these cytokines during asthma, we determined the role of GRK2 in regulating T cell-specific responses in our HMDE mouse model. We observed a significant reduction of airway hyperresponsiveness (AHR), lung eosinophil and lymphocyte counts, serum IgE, Th2 cytokines (IL-4 and IL-13), goblet cell hyperplasia and mucus production in mice that had reduced GRK2 expression specifically in T cells. Collectively, our studies reveal an important role for GRK2 in regulating T cell response during asthma pathogenesis and further elucidation of the mechanisms through which GRK2 modulates airway inflammation will lead to the development of new therapeutic strategies for asthma.